Analisis Selisih Biaya Produksi Pada UKM Krupuk Ikan Cita Rasa Di Kecamatan Talisayan - Andy Lisa Chomy (FAKULTAS EKONOMI DAN BISNIS UNIKARTA, 2019)
Abstract : The purpose of this research is to know the results of the analysis obtained from the difference between the standard costs of production with the actual costs of production and to know the cause. The usefulness of this research is can be used for information for business management to making process related to bending the costs of production or the efficiency the costs of production. Based on the data research in UKM Krupuk Ikan Cita Rasa acquired the profitable about Rp .11.464.006,-. The differenced was caused by volume and price materials changes. From the data above can be concluded that hypothesis can be accepted because of the analysis results of the difference between the standard cost it was greater than the factual cost proven by the cost production calculated gain Rp 11.464.006 , -. Keywords : Production Cost, UKM